From the Editor - Lovrenčić, Alen (Journal of Information and Organizational Sciences, 2024)
Dear readers, I had the pleasure of preparing the articles published in the Journal of Information and Organizational Sciences in the last four years. This is my issue, and I want to thank all who helped, every one in its way, the Journal to prosper. Firstly, I want to thank the authors who recognized JIOS as a decent journal adequate to publish their paper. Thanks to all the reviewers who helped me to classify received papers and raise the quality of the journal. Many of them were members of the editorial board which I want to address my thanks, too. The advisory board helped me to widen the pull of reviewers. At the end, I want to thank members of the publishing board who invested their time and work to improve the design of the journal and web page, and made it visible through the different journal bases. In the next issue, the function of the editor will be taken by Prof. Igor Balaban. I am sure that the Journal will become much better under his leadership. I wish good luck and pleasant work on our Journal to him and his team. Alen Lovrenčić